Eksplorasi Brand Love sebagai Faktor Kunci dalam Loyalitas Penonton Serial Barat - Kempa, Sesilya; Margo, Valerie; Indriyani, Ratih (IQTISHADequity jurnal MANAJEMEN, 2024)
This research examines the direct and indirect influence of emotional brand attachment, brand satisfaction and brand experience on brand love and customer loyalty of Western series viewers in Indonesia. Data was collected using a non-probability sampling technique using an online questionnaire distributed to 300 respondents quantitatively. This research analysis uses Partial Least Squares - Structural Equation Modeling (PLS-SEM). The research results show that emotional attachment, brand satisfaction, and brand experience significantly influence brand love. However, emotional attachment and brand experience do not have a direct influence on customer loyalty, highlighting the mediating role of brand love. Brand satisfaction is proven to be a key predictor of customer loyalty. These findings underscore the importance of building emotional connections, creating positive experiences, and ensuring audience satisfaction to drive loyalty through brand love. This research provides practical implications for Western series producers to increase audience engagement by integrating elements of cultural relevance, improving story quality, and utilizing social media platforms. Future research could explore additional factors influencing customer loyalty as well as examine different cultural contexts to broaden the generalizability of the findings.